Model Pengembangan Peningkatkan dan Pengelolaan Mutu Pendidikan di Sekolah - Marsya Al Farin; Najiha Azzahra; Amanda Putri Sari; Ibnu Majjah Arifin; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
Improving the quality of education aims to improve the quality of all Indonesian people through movement, ideology and sports to be able to compete in facing global challenges. The appointment of the importance of education aims to produce graduates who meet the requirements based on the potential of Indonesia's natural resources. Improving the quality of education is not only seen from one point of view, but covers all aspects of the educational process, ranging from inputs, processes, and results. The term management has connotations with the words management and administration. The word management is an English translation of the word management, but because the content is not representative in the content, the word management in Indonesian standardized into management. Education management is essentially a collaborative process that aims to achieve predetermined educational goals. Therefore, its existence is very important in the management of educational programs.